Ticagrelor pharmacokinetics and pharmacodynamics in patients with NSTEMI after a 180-mg loading dose. (3rd October 2017) - Holm, Manne; Tornvall, Per; Westerberg, Julia; Rihan Hye, Shaym; van der Linden, Jan
Abstract: The pharmacokinetics after a 180-mg loading dose (LD) of ticagrelor has not been thoroughly investigated in NSTEMI patients. We aimed to compare the ticagrelor uptake and on-treatment platelet reactivity between non-ST-segment elevation myocardial infarction (NSTEMI) patients and a control group of patients with stable coronary artery disease (SCAD) undergoing elective percutaneous coronary intervention. We performed an observational, prospective, single-center study including 40 NSTEMI patients and 20 SCAD controls. Key exclusion criteria included ongoing opioid treatment. Both groups received a 180-mg ticagrelor LD, and blood samples were taken pre-dose and 1, 2, 3, 4, 5, and 6 hours post-LD. Plasma concentrations of ticagrelor and its active metabolite AR-C124910XX were determined by validated methods. Platelet aggregation was tested using ADP-induced multiple electrode aggregometry. The primary endpoint was the time to maximal ticagrelor concentration (Tmax ). Clinical trial registration identifier number: NCT02292277. None of the pharmacokinetic variables differed significantly between the groups, including the Tmax of ticagrelor (2.0h [1.0–3.0] versus 2.0h [2.0–3.0], p = 0.393) and the active metabolite AR-C124910XX (3.0 [2.0–4.0] versus 3.0 [2.5–4.0], p = 0.289). High on-treatment platelet reactivity (HPR) was defined as > 46 aggregation units and was at one hour seen in 15% of the NSTEMI patients versus 10% of the controls (p = 1.0). At two hours post the 180-mg ticagrelor LD, 3% of the NSTEMI patients had HPR compared with none of the controls (p = 1.0). In conclusion, the uptake of ticagrelor was not significantly slower in NSTEMI patients not receiving opioids compared with the SCAD controls, leading to adequate onset of platelet inhibition in both groups.